SENSITIVITY ANALYSIS AND LIGHTWEIGHT DESIGN OF AN AUTOMOBILE SLIDING DOOR - TIAN YongKang; GONG YunXi; ZOU Ping; HUANG DaWei; FU AiJun (Jixie qiangdu)
Aiming at the sliding door of an automobile as the research object, a comprehensive finite element model of the sliding door based on the modal frequency and stiffness is established. The components with relatively small sensitivity are selected as the design variables through sensitivity analysis. The sample data of the thickness of key components are designed by using the Hamersley sampling test design method. The calculation results are fitted with the sliding door mass, first-order bending modal frequency. Approximate model of first-order torsional modal frequency, torsional stiffness and vertical stiffness response. Based on the approximate model, taking the minimum mass as the main objective and the maximum first-order bending frequency as the reference objective, and taking the first-order torsional mode of sliding door torsional stiffness and vertical stiffness as constraints, the multi-objective optimization algorithm based on global response surface method in Hyperstudy is applied to optimize the design to achieve the purpose of lightweight.